Urban Land Economics - Luque, Jaime (Springer, 2015)
This book covers the main aspects of regional and urban economics and presents state-of-the-art theories in a comprehensive and concise way. The book will be of interest to undergraduates in business and economics and covers specific areas such as real estate, urban and regional planning and geography and development studies.